Regulatory outlook from concept to commercialization of Biosimilars in Brazil market - Shekhar, Raj; Muralidharan, P; Hallur, Namrata; Puranik, Sangamesh B (Asian Journal of Pharmaceutical Research and Development, 2020)
Biological products or biopharmaceuticals are medicinal products derived from living organism systems and manufactured by using modern biotechnology that differ widely from the conventional synthetic drugs. They are much larger and more complex molecules with inherent diversity; hence, different manufacturers cannot produce identical biological products, even with the same type of host expression system and equivalent technologies. Thus, biologics manufactured and marketed after patent expiration are usually referred to as biosimilars. Biosimilars endeavor to copy the original technology leading to the production of innovative biotechnological medicines to obtain a product which is similar to the reference product. These products reported to improve the treatment landscape for multiple diseases, particularly in the areas of oncology, blood disorders, rheumatology, endocrinology and are becoming choice of treatment regimen due to policy push by governments for it’s affordability without comprising on quality, safety and efficacy. Pharmaceutical exports from Brazil increased by around 41% between 2009 and 2013, touching a high of U.S. $1.516 billion. The valuation of Brazilian pharma markets has shown double digit growth in the past decade. Between 2012 and 2015, market valuations have increased from U.S. $25.2 billion to U.S. $35.3 billion. Biosimilarity is based on a comprehensive comparability exercise wherein unavoidable clinical differences are evaluated and must meet equivalence or non-inferiority criteria. Biosimilars need to comply with different regulatory requirements for market authorization in different sites. There are several other related issues that need to be defined by the national authorities, such as interchangeability, labeling and prescribing information. The Brazilian health surveillance agency shadows the key principles established by the World Health Organization for the assessment of biosimilarity. However, the regulations also widen the gap by having standalone application pathway that does not require the usual comparability exercise with the reference product, originating non-biosimilar copies. Interchangeability and the use of nonproprietary names are not regulated. The objective of this manuscript is to explore the Brazilian Regulatory outlook from concept to commercialization of Biosimilars.